Exploring factors militating against the performance of parastatals in Zimbabwe: the case of the National Railways of Zimbabwe from 2008 to 2016 - Chilunjika, Alouis; Mutizwa, B. (Journal of Public Administration and Development Alternatives, 2022)
Parastatals in Zimbabwe have been underperforming and thus becoming a financial burden to the central government. They became havens of inefficiency and ineffective, vehicles of derailing intended strategies culminating in unrealised strategies. The period of the study is imperative as it was characterised by hyper- inflation which led to closure of some parastatals leading to dysfunctional of the public sector. This article gives an outline of factors which are standing as an impediment to the success of the National Railways of Zimbabwe. Data was collected using the mixed method approach and interviews were conducted, questionnaires were distributed, documents were also reviewed and analysed using content and thematic analysis. The research revealed that corporate governance epidemics, poor governance and mismanagement, financial distress, corruption, political interference, economy of affection, partisan and militarisation of the organisation as well as international isolation are all complementing each other in militating against the performance of the railway. The study recommends panacea actions which can be implemented to enhance effective and efficiency in the organisation.